Teacher Characteristics and Children’s Educational Attainment in Ghana: Do Some Teacher Characteristics Matter More for Children Attending Disadvantaged Schools? - Nyatsikor, Maxwell Kwesi; Sosu, Edward M.; Mtika, Peter; Robson, Dean (Frontiers in Education, 2020)
This study examined the association between teacher characteristics and primary school children’s educational attainment. Additionally, it explored whether certain teacher characteristics are more important for children attending disadvantaged schools. Multilevel analyses of linked administrative data on teacher characteristics and attainment indicate socio-economic differences in children’s educational outcomes. Teacher certification and experience were associated with children’s attainment in both Mathematics and English language. Findings exploring the differential effect of teacher characteristics show that teacher certification and experience were more important for the attainment of children attending rural and public schools. The results have significant implications for teacher professional development and deployment policies to improve attainment for all learners.